3(3x-1)+5=6(X+2)

Simple and best practice solution for 3(3x-1)+5=6(X+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x-1)+5=6(X+2) equation:


3(3x-1)+5=6(x+2)

We simplify the equation to the form, which is simple to understand
3(3x-1)+5=6(x+2)

Reorder the terms in parentheses
+(+9x-3)+5=6*(x+2)

Remove unnecessary parentheses
+9x-3+5=+6+*(+x+2+)

Reorder the terms in parentheses
+9x-3+5=+(+6x+12)

Remove unnecessary parentheses
+9x-3+5=+6x+12

We move all terms containing x to the left and all other terms to the right.
+9x-6x=+12+3-5

We simplify left and right side of the equation.
+3x=+10

We divide both sides of the equation by 3 to get x.
x=3.3333333333333

See similar equations:

| F(x)=2x-16x+31 | | 3x^2-7x-21=-1 | | 4(x-2)=5x+17 | | -4-7(5x-7)=49-39x | | x-89=176 | | 2q-5=8q+1 | | X+52+90+90=360 | | x^2-X=43.32 | | 40=-5m-5 | | 64+x=146 | | X=25+24 | | 2m^(3)n^(6)/10m^(2)n^(3) | | -3x+51+15x=3 | | 14+r=26 | | X=17+4 | | x^2+10x+18=x | | 4(3n-1.2)-0.5=9.5+0.2 | | x+77=394 | | X=29-9 | | 25x-20=15x+15 | | 4d+13-6-13.20= | | 45=3s | | 2x+3y=1700 | | 25=17+m | | X=28+22 | | 3d+13-6-13.20=1.55 | | X=21+11 | | 3d+13-6-13.20=1.60 | | 128+x+40+82=360 | | x+5.25=7.55 | | X=19+11 | | 3d+13-6-13.20=2.07 |

Equations solver categories